Investigating playing-related musculoskeletal disorders in South African instrumental musicians - Green, Erryn Mae (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
This study, one of the first studies in SA to investigate PRMD in a wideranging sample of instrumental musicians using a validated self-report tool, shows that PRMDs are highly prevalent among a range of SA musicians and have a considerably negative effect on musicians' performance ability and quality of life. However, making inferences about most affected genre or instrumental group was challenging due to the small sample sizes in some categories. The results from this study confirm that the nature of PRMD development is indeed multi-factorial, with factors numerous individual and playing-related factors playing a role in the development of PRMDs in SA musicians. Better support and education on health promotion for musicians, including awareness of and prevention strategies for PRMDs in the SA context are needed which may reduce the prevalence of PRMDs.
Keywords: Musculoskeletal disorder; Musculoskeletal system Diseases; Musicians Wounds and injuries; Musicians Health and hygiene; Human engineering -- South Africa; Musicians Health risk assessment; Biomechanics; Musical instruments; Music genre